Ni‐Ti Codoped Hibonite Ceramic Pigments by Combustion Synthesis: Crystal Structure and Optical Properties. Issue 5 (7th February 2016) - Ardit, Matteo; Borcănescu, Silvana; Cruciani, Giuseppe; Dondi, Michele; Lazău, Ioan; Păcurariu, Cornelia; Zanelli, Chiara
Abstract : Hibonite (CaAl12 O19, space group [s.g.] P 63 / mmc ) has the structural formula A [ XII ] M1 [ VI ] M2 [V] M32 [ IV ] M42 [ VI ] M56 [ VI ] O19, where Ca is 12‐fold coordinated at site A and Al 3+ ions are distributed over five different sites: three distinct octahedra [M1 (point symmetry D3 d ), M4 (C3v ) and M5 (C s )], the M3 tetrahedron (C3v ), and the unusual fivefold coordinated trigonal bipyramid M2 (D3 h ). Hibonite is able to accommodate a wide range of ions with different valence and coordination, making its structure a promising ceramic pigment. One of the main challenges is to understand and control incorporation mechanisms and the threshold of chromophores solubility. It is known that M 2+ ions tend to be hosted at the M3 site, while M 4+ ions are preferentially accommodated at the M4 site: the introduction of divalent ions might be promoted by the associated incorporation of tetravalent cations, which ensure the lattice electroneutrality and are ordered over the M4 face‐sharing octahedral dimers. In this work, the mechanism of the coupled substitution 2Al 3+ →(Ni 2+ +Ti 4+ ) was investigated by combining X‐ray powder diffraction and diffuse reflectance spectroscopy techniques. Hibonite turquoise pigments with increasing Ni+Ti doping (CaAl12‒2 x Ni x Ti x O19 where x = 0.1‒2.0 apfu) were prepared by combustion synthesis, utilizing a fuel mixture (urea, glycine, β‐alanine) set up according to their compatibility with metal nitrates used as raw materials. The ignition temperature of combustion reaction was 400°C, but samples underwent an additional annealing at 1200°C. Samples up to x = 0.4 are monophasic; for higher doping, hibonite is the main component accompanied by growing percentages of spinel and perovskite phases. The Ni and Ti addition induced a regular increase in the hibonite unit‐cell parameters until x = 1.0, that is proportional to the amount and difference in ionic radii of dopants. In particular, an elongation of the 〈M–O〉 bond distances of both M3 and M4 sites was observed. In terms of optical parameters, Ni 2+ is preferentially incorporated in tetrahedral coordination, up to 0.3 apfu at the M3 site, and at the M4 octahedron as well (up to 0.19 apfu). The crystal field strength of fourfold coordinated Ni 2+ is regularly decreasing, implying an elongation of the local Ni–O bond that is coherent with the volume increasing from AlO4 to NiO4 tetrahedra registered by XRD. Ti 4+ ions are accommodated at both the M2 and M4 octahedra which expand proportionally to the amount of dopants. Pigment purity and color strength vary with doping depending on the multistep mechanism of Ni and Ti incorporation in the hibonite lattice.